Selected aspects of relations between Imperium Romanum and nomadic peoples - Żyromski, Marek (Balcanica Posnaniensia. Acta et studia, 2007)
The author addresses the issue of relations between the Roman Empire and nomadic peoples, with particular emphasis on the Principate period (27 BC–284 AD). The background to these considerations is Roman territorial expansion and the related questions about the existence of a coherent „grand strategy” or rather ad hoc responses to emerging threats. This issue is at the centre of contemporary historiographical debate. The aim of the article is to show the complexity of Rome's relations with nomadic peoples and to present the specific nature of the functioning of the empire's borders in various parts of the Mediterranean world and beyond. The analysis is based on ancient sources, literature on the subject and interpretations by contemporary researchers. The author uses a comparative method, juxtaposing models of defence and administration in the eastern, western and border provinces. The conclusions show that the Roman army performed not only military functions (attack and defence), but also economic, organisational and police functions, especially in newly conquered areas. The Roman limes was multifunctional – in addition to protecting the borders, it served to control trade and promote social integration. There were clear differences between the eastern and western provinces. Rome's relations with nomadic peoples were dynamic and adaptive, which testifies to the flexibility and long-term effectiveness of Roman border policy.